On generalized principally quasi-baer modules (2013)
Let R be an associative ring with identity. A right R-module M is called generalized principally quasi-Baer if for any m 2 M, rR(mR) is left s-unital as an ideal of R and the ring R is said to be right (left) generalized principally quasi-Baer if R is a generalized principally quasi-Baer right (left) R-module. In this paper, we investigate properties of generalized principally quasi-Baer modules and right (left) generalized principallyquasi-Baer rings.